Kedudukan Balu Luh di Desa Adat Suter Bangli - I Made Suriana; I Made Suwitra; Diah Gayatri Sudibya (Jurnal Preferensi Hukum, 2020)
The patrilineal descent system, as is also the case in the indigenous Balinese, has the consequence that the heirs in Bali are determined according to the male lineage (purusa). However, it is also possible for women to be appointed as heirs, that is, in the case of the girl being appointed as a sentana rajeg or the status of a girl is changed from predana to purusa status. Based on the background of this research problem formulation as follows: how is the obligation for the manners of Balu Luh in the Suter Bangli Customary Village and how the authority of the manners for the inheritance of her husband. The type of research used is empirical legal research. The results of this research discussion are as follows: Obligations for manners in the village of Suter Bangli, among others, take care of the inheritance of her deceased husband well, behave well, enforce discipline, obey the obligations, carry out obligations, panca yadnya and others, which are then referred to as her husband's legacy properly balu pageh, the widow's right as long as only enjoying it can not sell, give, and give it to others except with the consent of her children and the family of her late husband if her children are still small. This applies to heirlooms and riches (marriage assets), because for heirlooms, a widow does not have any rights, the right is the purusa of the family of her deceased husband, but the widow has the right to enjoy it if the widow is pageh. The authority of the courtesy of her husband's inheritance includes: Maintaining the integrity of the family, not doing things that are not good, so that it can be called a shame. No authority to sell, transfer the assets left by her late husband. May ask for children / sentana, but with the consent of the family of the late husband. May also remarry with the approval of the family of the late husband.